City-to-city learning within climate city networks: definition, significance, and challenges from a global perspective. Issue 2 (3rd May 2020) - Haupt, Wolfgang; Chelleri, Lorenzo; van Herk, Sebastiaan; Zevenbergen, Chris
ABSTRACT: Cities are increasingly joining forces through transnational municipal networks. The presented research focuses on one of the key services of these organisations: providing a platform for city-to-city learning. Interviews with representatives of networks and cities showed that through network organisations local policymakers aim to connect with peers from cities that face similar challenges or that are considered frontrunners. However, the main perceived added value of the studied network organisations is around their function as facilitator of personal networking among local policymakers. While learning certainly takes place and is actively promoted by some networks, most peer-exchanges are about the sharing of knowledge and do not qualify as learning. Therefore, we suggest to distinguish thoroughly between mere 'knowledge sharing' and processes of in-depth learning. Moreover, we call for more research focussing on the role of frontrunner cities in providing 'solutions', particularly up to which point these are helpful and down-scalable